Effects of the application of pulsed combination therapy associated with medium frequency excitomotor current under the reduction of abdominal localized fat in women (Research, Society and Development, 2020)
The present study investigated the effects of the application of combined therapy in a pulsed manner associated or not with the medium-frequency excitomotor current in women for the treatment of localized fat reduction, effects on blood pressure and on the autonomic nervous system. This is a clinical trial randomized study, made up of women who underwent combined therapy treatment over 12 combined. The variables analyzed were anthropometry, heart rate variability and blood pressure. With a decrease in localized fat in the group with an association of excitomotor current, HRV did not yield results, suggesting future studies with the cardiac population.